Recurrent petrositis due to nasopharyngeal carcinoma in an adult patient: Gradenigo's syndrome - Aksoy, Asude; Varoglu, Asuman Orhan (Wolters Kluwer Medknow Publications, 2018)
The early diagnosis of very rare nasopharyngeal carcinoma (NPC) is so difficult, to surrounded by structures such as the orbital skull base. With the invasion of the disease, the symptoms are manifested in different ways so that it may be confusion and delay in diagnosis and treatment in this situation. Including otological symptoms (serous otitis media), Gradenigo's syndrome is a rare clinical condition. The majority of published cases involve children, and the most common etiology is otitis media. We report a case of a diabetic man who presented with repeating Gradenigo's syndrome symptoms due to NPC.
Keywords: Gradeningo's syndrome; mastoiditis; nasopharyngeal carcinoma